Infections seem to be more frequent before onset of pediatric multiple sclerosis: A Danish nationwide nested case–control study. (May 2019) - Boesen, Magnus Spangsberg; Koch-Henriksen, Nils; Thygesen, Lau Caspar; Eriksson, Frank; Greisen, Gorm; Born, Alfred Peter; Blinkenberg, Morten; Uldall, Peter Vilhelm; Magyari, Melinda
Background: Infections are suspected environmental triggers for multiple sclerosis (MS). The relationship between the timing and cumulative number of childhood infections regarding pediatric MS risk is uninvestigated. Objectives: To investigate whether childhood infections contribute to pediatric MS. Methods: A nationwide nested case–control study with detailed MS case ascertainment including chart review was undertaken. For each MS case, we selected five control children using density sampling from the entire Danish population, matching controls to children with MS by sex and birthdate. We analyzed data with the cumulative number of childhood infections as exposure and MS as outcome. Hazard ratios (HRs) including 95% confidence intervals (CIs) were estimated using Cox regression. Results: We identified 212 children with MS and 1, 060 controls. Median age at MS onset was 15.3 years (range: 7.6–17.8 years); 72% were girls. Each infection during the preceding 3 years increased the hazard for MS by 11% (95% CI = 1.01–1.22, p = 0.04); having 5+ infections compared with 0–4 infections in the preceding 3 years doubled the hazard for MS (HR: 2.18; 95% CI = 1.12–4.30, p = 0.02). Conclusion: Children with MS appeared to have more infections in the 3 years preceding MS clinical onset; accordingly, immune response to infections may influence MS pathogenesis.